Growth of helical carbon nanofibers in the presence of Ni-Cu catalysts - Jung, Hyun-Seung; Lee, Seung Yong; Ahn, Jae-Pyoung; Park, Jong-Ku (KOREAN INST METALS MATERIALS, 2006)
Carbon nanofibers (CNFs) are synthesized by the dissociation of ethylene gas in the presence of Ni-Cu alloy catalysts; helical CNFs are favored by Ni-Cu alloy catalysts. The role of alloy compositions and reaction time in the morphology of CNFs were determined by varying both the Cu content in the alloy catalyst and the holding time at a particular synthesis temperature. The chemical composition, the size, and the shape of the catalyst particles were shown to affect the morphology of CNFs. Two kinds of growth mechanism are suggested to explain the growth of helical and straight CNFs.
Keywords: FORMATION MECHANISM; FILAMENTOUS CARBON; DECOMPOSITION; NICKEL; ACETYLENE; METHANE; DEPOSITION; PYROLYSIS; NANOTUBES; NANOCOILS